Indicators of psychiatric disorder among women admitted to prison. - Turner, T H (1986)
A random sample of 708 women prisoners recently admitted to Holloway Prison was screened for evidence of psychiatric disorder. Of the 708 women, 195 had a history of self harm, 44 of whom had a history of cutting themselves, 125 had a history of psychiatric illness, 99 were dependent on opiates, and 89 took psychotropic drugs regularly. These findings suggest that there is a need for psychiatric units in women's prisons such as Holloway Prison, and that initiatives to alter policies of admission to psychiatric hospitals should be pursued.